Childhood trauma and brain structure in children and adolescents. (February 2023) - Peverill, Matthew; Rosen, Maya L.; Lurie, Lucy A.; Sambrook, Kelly A.; Sheridan, Margaret A.; McLaughlin, Katie A.
Abstract: The dimensional model of adversity proposes that experiences of threat and deprivation have distinct neurodevelopmental consequences. We examined these dimensions, separately and jointly, with brain structure in a sample of 149 youth aged 8–17—half recruited based on exposure to threat-related experiences. We predicted that greater threat would be uniquely associated with reduced cortical thickness and surface area in brain regions associated with salience processing including ventromedial prefrontal cortex (vmPFC), anterior cingulate cortex (ACC), and insula, and that deprivation experiences would be uniquely associated with reductions in cortical thickness and surface area in frontoparietal areas associated with cognitive control. As predicted, greater threat was associated with thinner cortex in a network including areas involved in salience processing (anterior insula, vmPFC), and smaller amygdala volume (particularly in younger participants), after controlling for deprivation. Contrary to our hypotheses, threat was also associated with thinning in the frontoparietal control network. However, these associations were reduced following control for deprivation. No associations were found between deprivation and brain structure. This examination of deprivation and threat concurrently in the same sample provided further evidence that threat-related experiences influence the structure of the developing brain independent of deprivation. Highlights: Threat-related experiences were associated with thinner cortex in multiple areas. Threat-related thinning spanned salience, default, and somatomotor networks. This thinning was robust to control for deprivation experiences. Younger, threat-exposed participants had smaller amygdala volumes.